Extraction of Potassium from Biotite by Sr2+/K+ Exchange Method and Electrochemical Properties of Hydrated Sr-Mica. (November 2019) - Yao, Donghui; Huang, Zhiliang; Pan, Bingbing; Zhao, Zhouqiao
Abstract: Soluble potassium has been successfully extracted from biotite by Sr 2+ /K + ion exchange. The hydrated Sr-mica after ion exchange has better electrochemical properties. The potassium extraction rate, mica silicate structure and electrochemical properties (charge-discharge and cycling properties) before and after ion exchange were characterized by X-ray fluorescence spectroscopy, powder X-ray diffraction, Fourier Transform Infrared spectrometer and constant current charge-discharge cycle technology. The results show that after 10 hours of strontium ion exchange, the layered silicate structure is not destroyed. The maximum potassium extraction rate is 98%. The biotite gradually transforms into vermiculite strontium mica to form strontium mica, and the basal (001) spacing expands from 1.001 nm to 1.517 nm. The electrochemical properties of hydrated Sr-mica obtained after exchange have been improved.